2002
DOI: 10.1002/jcb.10195
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of protein tyrosine phosphatase PTP‐MEG2

Abstract: PTP-MEG2 is an intracellular protein tyrosine phosphatase with a putative lipid-binding domain at the N-terminus. The present study reports expression, purification, and characterization of the full-length form of the enzyme plus a truncated form containing the catalytic domain alone. Full-length PTP-MEG2 was expressed with an adenovirus system and purified from cytosolic extracts of human 293 cells infected with the recombinant adenovirus. The purification scheme included chromatographic separation of cytosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 33 publications
1
30
1
Order By: Relevance
“…When the lipid is present, PTP-MEG2 dephosphorylates one or several substrates involved in secretory vesicle fusion and/or homeostasis. This model is supported by the recent finding that PTP-MEG2 lacking its Sec14p homology domain has a considerably higher activity than the full-length enzyme (42). Thus, the Sec14p homology domain appears to be involved in intramolecular regulation of the catalytic activity of PTP-MEG2.…”
Section: Discussionmentioning
confidence: 59%
“…When the lipid is present, PTP-MEG2 dephosphorylates one or several substrates involved in secretory vesicle fusion and/or homeostasis. This model is supported by the recent finding that PTP-MEG2 lacking its Sec14p homology domain has a considerably higher activity than the full-length enzyme (42). Thus, the Sec14p homology domain appears to be involved in intramolecular regulation of the catalytic activity of PTP-MEG2.…”
Section: Discussionmentioning
confidence: 59%
“…Although the function and lipid binding specificity of the domain in the context of other RhoGEFs has yet to be determined, recent studies of the Sec14 homology domain of the protein phosphatase MEG2 demonstrated that this domain is responsible for regulation of the MEG2 catalytic activity (61) and that it modulates intracellular localization of the protein though specific binding to phosphatidylserine (62). Our demonstration that the Sec14 domain of Dbs has similar properties suggests a conserved function for these sequences in the context of mammalian proteins.…”
Section: Figmentioning
confidence: 70%
“…However, with a nonfusion protein purified from an adenovirus expression system, we failed to show such an activation. 23 Instead, our recent studies demonstrated a specific binding of PTP-MEG2 with phosphatidylserine through the putative lipidbinding domain but the lipid does not activate the enzyme in vitro. 36 What activates PTP-MEG2 PV ECFCs remains to be identified.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies showed that removal of the N-terminal domain significantly activated the enzyme, suggesting its regulatory role. 23,32 Furthermore, PTP-MEG2 has been shown to be partially localized in intracellular membranes at the secretory vesicles. 32,33 In this study, we have demonstrated that PTP-MEG2 is present in both cytosol and membrane fractions of ECFCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation